Thermal decomposition of ipil-ipil and kakauate - Ong, Richard (Animo Repository, 1989)
The study concerns the decomposition of ipil-ipil and kakauate in the absence of oxygen. Three different shapes of wood samples cubes (sides = 2 cm), slabs (length = 4 cm, width = 2 cm, height = 1 cm) and cylinders (length = 2.20 cm, diameter = 2.14 cm) were considered, and each tested under an inert nitrogen gas atmosphere, at temperatures of 200 C, 300 C, 400 C and at time intervals of 0.5, 1, 2, and 3 hours for each temperature. These variations were made to determine the effect of this parameters on charcoal yield.The study showed that charcoal yield of the wood sample increases from 200 C to 400 C and from 0.5 hours to 3 hours. At 200 C and 300 C, charcoal yield varied for the three shapes used but at 400 C, charcoal yield were almost the same. This is true for both ipil-ipil and kakauate. Lastly, at the same conditions of time, temperature and shape, ipil-ipil had a higher charcoal yield over kakauate.